Household Food Systems during Lockdown: Food Diaries of Filipino Mothers in Poor Urban and Sub-urban Households - Quetulio-Navarra, Melissa (Archīum Ateneo, 2024)
Studies have documented the erosion of the country’s food systems due to government impositions, but at household level the COVID-19 pandemic-impacted food system of lower-class Filipino households was only examined in terms of nutritional quality. The present study aims to report on how aid-dependent household food systems are functioning in the everyday lifeworld of poor households. Using the solicited diary method, we collected the lockdown experiences of ten women from two resettlement communities in managing the pandemic food system. The household food system in both communities has had to adapt to pandemic-induced uncertainties and, at the same time, has been shaped by aid in the form of food and cash from relatives, friends, neighbours, governments (national and local), and non-government organizations. We found that recipients tend to prefer cash assistance over food aid, due to the increase in freedom and the potential to improve overall welfare of the household members. The results also showed that women are at the helm of making the food system work for the household. We found that women are goal-driven and strategic in rationing the food and preparing the meals. The value of aid for the households goes beyond its food security objective; it also contributes to maintaining the women’s psychological well-being and strengthening their spirituality during the crisis. Nevertheless, government’s social targeting of aid could be improved, and food and nutrition security interventions could be more professionally dealt with.